DEVELOPMENT OF THE DECISION MAKING SYSTEM FOR OPTIMIZATION OF FOUNDRY TECHNOLOGIES - E. I. Marukovich; V. A. Pumpur; V. G. Gruzovskij (Литьë и металлургия)
The program complex, which is the basis of decision taking system for optimization of foundry technologies, is presented in the article. The method of optimization is built on the principles of the fuzzy sets theory